The Influence of Competence and Work Discipline on The Performance of Sari Ater Hot Spring Resort Subang Employees: English - Priyanto, Rahmat; Kamalah, Nurul (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Sari Ater Hot Spring Resort is one of the popular tourist destinations in Indonesia. It is known for its natural hot springs and is located in the Subang region of West Java. These hot springs are formed from volcanic activity in the area. The mineral-rich hot water is believed to have various health benefits, making it an attraction for people seeking relaxation, relief from muscle pain, or simply a place to unwind. This study aims to determine the influence of competence and work discipline on employee performance at Sari Ater Hot Spring Resort Subang, both partially and simultaneously. The method used in this research is a quantitative method with a descriptive and verification approach. Data was collected by distributing questionnaires to 250 respondents, using validity tests, reliability tests, SEM AMOS, and hypothesis testing. This study's results indicate no significant influence between competence and employee performance at Sari Ater Hot Spring Resort. However, there is a significant influence between work discipline and employee performance at Sari Ater Hot Spring Resort. Furthermore, the simultaneous statistical test results show that competence and work discipline together impact employee performance at Sari Ater Hot Spring Resort